Oral Corrective Feedback: What do Students Prefer and Why? - Candra Hadi Asmara; Prativi Khilyatul Auliya; Ribeh Najib Muhammad (TLEMC (Teaching and Learning English in Multicultural Contexts), 2022)
Corrective feedback is crucial for students to improve their speaking skill. The feedback is as important as the way of delivering it to students. Lecturers need to acknowledge students’ preferences on corrective feedback, so it will be useful for students’ speaking improvement. This study aims at investigating (1) the amount of corrective feedback that students think most useful and its reason, (2) types of corrective feedback that students think most useful and its reason. This study utilizes mixed method. Both close-ended and open-ended questionnaire are used to gain the data. The result shows that students need the lecturer to mark all their errors during speaking. When lecturer marks all their error, they will remember the correction and will never repeat the same mistake in the future. Furthermore, students also need the lecturer to mark their mistakes every time they make it to avoid them making the same mistake on the other occasion. In this study, most students prefer explicit correction as the useful way that can be done by lecturer to deliver the corrective feedback. Students need lecturer to do that way to give feedback in term of grammar, pronunciation and vocabulary or word choice. Explicit correction is saving time since it does not need further explanation why a certain word’s choice, word’s pronunciation or grammar is incorrect. It is also efficient because lecturer does not need to wait for students to think about or to guess the right form of certain word’s choice, word’s pronunciation or grammar.Keywords: Oral Corrective, Feedback, Students’ Preference, Speaking Skill